Viewing, listening and reading along: Linguistic and multimodal constructions of viewer participation in the net series SKAM - Andersen, Elisabeth Muth; Poulsen, Søren Vigild (Scandinavian Studies in Language, 2019)
This paper investigates how SKAM viewers are positioned as participants through semiotic resources in the net series, i.e. the filmic means for making meaning, including representations of the characters’ embodied and digitally mediated communication. For this purpose, we combine perspectives from linguistic-multimodality studies of modes for communication and studies building on Goff man’s (1981) work on participation frameworks, i.e. the various ways of participating in co-present and/or mediated communication. The article aims to complement existing media studies of immediacy in SKAM and viewers’ sense of co-presence with characters in the net series (Jerslev 2017, Sundet 2017). It does so by showing how participant frameworks are multimodally constructed at a fictional level and a communicational level. Within each of these frameworks, the viewer is positioned in distinct ways. We describe how the viewer is placed, i.e. physically positioned, in the interactional space of the depicted characters, and how the characters’ communicative means are interactionally organised, accomplished and made available for interpretation by the viewer. Furthermore, we show how characters monitor each other in the shared space of a schoolyard, how embodied and digitally mediated communicative features are foregrounded, and how the viewer is provided access to these resources in ways that reflect and create specific viewing positions in the communicative frames of the characters. We argue that these integrations of semiotic modes exploit affordances related to speech, writing and embodiment, that the positionings mainly work to create a sense of presence and identification for the viewer, and that representations of digitally mediated communication (writing) on the viewer’s screen specifically expose how the digitally mediated communication space of one of the characters is integrated with the digitally mediated viewing space.